Female Tactical Members in Correctional Services: “No Room for Women” - Kakuk, Melissa (Women & criminal justice, 2020)
This exploratory study examines the experiences of female correctional officers in one Canadian jurisdiction who have been members of tactical teams within correctional services and identifies social and systemic factors that affect female officers’ participation on tactical teams. Overall, masculine hegemony impacts organizational culture where the roles of female officers remain constrained within traditional gender stereotypes. Tactical members on all-female teams reported more positive experiences than those on integrated teams. This study represents the first known examination of female tactical officers in correctional services.